Influence of Organic Leaf Fertilizer on Development of Jabon Seedling Growth (Anthocephalus cadamba Roxb. Miq.) - Arum Sekar Wulandari; Anindita Julian (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Jabon with good quality can be gained by adding nutrient to plant through fertilizer. This research aims to increase the growth of jabon through the application of X organic leaf fertilizer. The research was conducted in greenhouse with using the randomized complete design (RAL). X organic leaf fertilizer applied to jabon seeds every 2 weeks during the 16 weeks. The variables are height, diameter, fresh weight of shoot and root, dry weight of shoot and root, length of root, root shoot ratio and seed quality index. The results showed that 3 variables out of 9 variables are significantly affected to the growth of jabon seeds, such as height, fresh weight and dry weight of shoot. The application of X organic leaf fertilizer with 0.4% concentration can increase 10.62 cm height of jabon seeds (20.14%), 8.24 grams fresh weight of shoot (66.1%) and 1.26 grams dry weight of shoot (72.60%).